2016
DOI: 10.1177/0309132516645960
|View full text |Cite
|
Sign up to set email alerts
|

Understanding domestic violence in rural spaces

Abstract: This paper responds to calls for geographers to engage critically with the claim that 'violence sits in places' in the analysis of domestic violence in rural areas. It argues the need to develop conceptual understandings of the spatialized and embodied experience of domestic violence in the countryside. Drawing on debates about what counts as violence and on feminist work on domestic violence as intimate terrorism, the paper explores ways in which experiences of violence (and associated fear) are shaped by par… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
32
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 53 publications
(32 citation statements)
references
References 49 publications
0
32
0
Order By: Relevance
“…Violence in rural localities can be exacerbated by geographic isolation, the presence of, and easy access to, firearms, a patriarchal culture with more defined gender roles than those found in urban areas and women being coerced to keep private what goes on within their homes (Wendt & Zannettino, 2015). Pressure to keep secrets may be more pronounced in rural communities where people are interconnected through family relationships and social activities and privacy is carefully protected (Little, 2017). Help can be difficult to access due to a lack of rural social and legal services and/or poorly funded and understaffed social services.…”
Section: Original Articlementioning
confidence: 99%
See 1 more Smart Citation
“…Violence in rural localities can be exacerbated by geographic isolation, the presence of, and easy access to, firearms, a patriarchal culture with more defined gender roles than those found in urban areas and women being coerced to keep private what goes on within their homes (Wendt & Zannettino, 2015). Pressure to keep secrets may be more pronounced in rural communities where people are interconnected through family relationships and social activities and privacy is carefully protected (Little, 2017). Help can be difficult to access due to a lack of rural social and legal services and/or poorly funded and understaffed social services.…”
Section: Original Articlementioning
confidence: 99%
“…One aspect of rural intimate partner violence is the use of geographic isolation to reinforce control. International research has identified that geographic isolation can be used as a form of entrapment by the perpetrators of intimate partner violence (Edwards et al, 2014;Faber & Miller-Cribbs, 2014;Little, 2017;Mason, 2012;Wendt, 2009;Wendt et al, 2017). By removing their partner from social support and geographically isolating them, perpetrators are able to have more control.…”
Section: Experiences Of Intimate Partner Violencementioning
confidence: 99%
“…We consider these socio-spatial and legal realities initially at the scale of the body (Massey, 1993;Marston, 2000), which demands a simultaneous recognition of law as both embodied (Philippopoulos-Mihalopoulos 2014: 55;Pruitt, 2008a;Siegel, 1992) and emplaced, i.e., as determining when and how much distance is legally salient. Acknowledging the lived quality of a legally imposed distance does more than render visible so many intersecting invisibilities: it arguably induces a more just and empathic recognition of both structural interpellation and a woman's individual agency (Little, 2016: 3) in the context of restricted access to abortion services.…”
Section: © Michelementioning
confidence: 99%
“…Felix also noted the added costs of abortion for women who already had children, who must either find child care or take their children with them, thereby incurring additional costs and delays for "eating, napping, and/or power of women (Little, 2016) , to see how in every facet of their lives they were really tried to be made invisible-and yet… these women were really finding their voice as a community on an issue that could be politically ostracizing, and were willing to use whatever, if any, political power-we want to talk about our healthcare, our bodies-to reframe this issue as a healthcare crisis… The way that they were organizing, their willingness to step out of the shadow that was engulfing them in so many ways….…”
Section: © Michelementioning
confidence: 99%
“…Largely, it is argued that these gendered experiences and beliefs of (hetero)romance are implicated by the privileging of heteronormative‐gendered roles within rural areas. What also is argued is that this privileging of heteronormativity correlates with the statistically higher rates of oppressive strategies—ranging from the use of violence to the practice of surveillance—that men are able to use to control their romantic partners (Carrington and Scott ; DeKeseredy ; Little ). This article contributes to these bodies of work by analyzing how young men (all aged 16) from a rural high school in Aotearoa/New Zealand talked about the rules of being boyfriends, and in particular one specific theme that emerged which concerned the practice of “territory marking”—“men fight[ing] other men over women” (Flood :346).…”
Section: Introductionmentioning
confidence: 99%